Serum Metabolomic Profiling Reveals the Amelioration Effect of Methotrexate on Imiquimod-Induced Psoriasis in Mouse - Zong, Jiaxin; Cheng, Jieyi; Fu, Yuanfeng; Song, Jing; Pan, Weisong; Yang, Li; Zhang, Ting; Zhou, Mingmei (Frontiers in Pharmacology, 2020)
Background: The imiquimod-induced psoriasis mouse model has been used as a model for pathogenic mechanism research, and methotrexate is widely employed to treat various clinical manifestations of psoriasis. We explored the underlying pathogenesis of psoriasis and the treatment mechanism of the conventional drugs from the metabolic perspective of the psoriasis mouse model. Methods: Male BALB/c mice were smeared imiquimod (IMQ) for 7 days to induce treatment-resistant psoriasis and intragastrically administered MTX. We evaluated inflammation of psoriasis-like lesions and therapeutic effect of MTX based on histological changes and immunohistochemistry. Comprehensive metabolomics analysis based on gas chromatography-mass spectrometer (GC-MS) detection of serum samples was performed to identify the alteration of metabolites. Results: It was found that MTX ameliorated psoriatic lesions (representative erythema, scaling and thickening) by inhibiting proliferation and differentiation of keratinocytes. Multivariate statistical analysis of metabolomics data displayed alterations in serum metabolites among mice of the control (Con) group, IMQ group and MTX group. Compared with Con group, psoriasis mice had the higher level of d-galactose and lower expression of myo-inositol, 9,12-octadecadienoic acid, cholesterol; In contrast with model set, serum levels of glycine, pyrrolidone carboxylic acid, d-galactose, d-mannose were significantly decreased in MTX group. Conclusions: The differential metabolites, reflecting the perturbation in the pathways of inositol phosphate metabolism, glycine, serine and threonine metabolism, glyoxylate and dicarboxylate metabolism, glutathione metabolism, and glucose metabolism, could contribute to the pathogenesis of psoriasis and were also involved in the pharmacological regulation of MTX. This study established the foundation for further research on the mechanism and therapeutic targets of psoriasis.